1975
DOI: 10.1099/00221287-87-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Salmonella typhimurium Conferring Resistance to Felix O Phage without Loss of Smooth Character

Abstract: S U M M A R YSeveral mutants obtained from smooth SalmoneIla typhimurium strains by selection for resistance to Felix 0 (FO) phage [whose receptor site includes the N-acetylglucosamine branch of the lipopolysaccharide (LPS) core] were smooth in cultural properties, antigenic character and phage sensitivity pattern (except for their FO resistance). However, the affected genes of several such 'FOR' (FOresistant) mutants were shown by transduction to map in the short cysE-pyrE segment, which includes nearly all k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 12 publications
2
47
0
Order By: Relevance
“…MacPhee et al (1975) found that the FOR strain SL4504 was still virulent for mice, whereas SL4505 was not. The amount of LPS and the average length of 0 side-chain was virtually the same for the two FOR strains.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MacPhee et al (1975) found that the FOR strain SL4504 was still virulent for mice, whereas SL4505 was not. The amount of LPS and the average length of 0 side-chain was virtually the same for the two FOR strains.…”
Section: Discussionmentioning
confidence: 99%
“…The FOR strains differ from their smooth parent strains primarily by being resistant to the FO phage, for in cultural and serological properties the FOR mutants were almost identical to the smooth strains (MacPhee et al 1975). This investigation was performed in order to try to analyse whether there were either qualitative or quantitative differences between LPS from FOR mutants and LPS from the parent strain, even if these could not be No LPS could be extracted from any of these strains by the PCP method.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations